2021
DOI: 10.3390/pharmaceutics14010074
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Hydrophilic Small Molecules to Retinal Cell Lines Using Gel Core-Containing Solid Lipid Nanoparticles

Abstract: In this study, we developed a novel solid lipid nanoparticle (SLN) formulation for drug delivery of small hydrophilic cargos to the retina. The new formulation, based on a gel core and composite shell, allowed up to two-fold increase in the encapsulation efficiency. The type of hydrophobic polyester used in the composite shell mixture affected the particle surface charge, colloidal stability, and cell internalization profile. We validated SLNs as a drug delivery system by performing the encapsulation of a hydr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In a previous study, we demonstrated the importance of a liquid core to load hydrophilic molecules, like nucleic acids. 74 In this view, microfluidics offered two huge and unexpected advantages for the delivery of pDNA over the limited standard post-modification approach normally seen in the literature. First, the “pre” addition allowed to have almost 100% of pDNA bound to LNPs even with 100 µg/mL while maintaining their physical characteristics, which fall within the limits for good biodistribution and monodispersity, compared to the “pre” addition leading to poor NMed formation even at only 15 µg/mL, demonstrating how when this new technique is optimized could be incredibly advantageous for gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the importance of a liquid core to load hydrophilic molecules, like nucleic acids. 74 In this view, microfluidics offered two huge and unexpected advantages for the delivery of pDNA over the limited standard post-modification approach normally seen in the literature. First, the “pre” addition allowed to have almost 100% of pDNA bound to LNPs even with 100 µg/mL while maintaining their physical characteristics, which fall within the limits for good biodistribution and monodispersity, compared to the “pre” addition leading to poor NMed formation even at only 15 µg/mL, demonstrating how when this new technique is optimized could be incredibly advantageous for gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PARP may indirectly activate calpains via its excessive consumption of NAD + and a resultant breakdown of cellular energy metabolism [ 25 ]. Loss of intracellular ATP will impair the function of plasma membrane Ca 2+ ATPase (PMCA), an active transporter that is crucial for keeping intracellular Ca 2+ levels low [ 65 ]. Remarkably, HDAC inhibition has been found to increase PMCA activity [ 66 , 67 ], which thus could enhance intracellular Ca 2+ clearance and reduce calpain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of NPs was assessed as previously published [ 57 ]. Briefly, 661W-A11 cells were cultured in 96-well plates at a density of 6000 cells/well and increasing dilutions of NPs were added to the culture medium.…”
Section: Methodsmentioning
confidence: 99%